A self-assembled nano-cluster complex based on cytochrome c and nafion: An efficient nanostructured peroxidase - Hong, Jun; Wang, Wei; Huang, Kun; Yang, Wei-Yun; Zhao, Ying-Xue; Xiao, Bao-Lin; Gao, Yun-Fei; Moosavi-Movahedi, Zainab; Ahmadian, Shahin; Bohlooli, Mousa; Saboury, Ali Akbar; Ghourchian, Hedayatollah; et al. (Biochemical engineering journal, 2012)
► Highly efficient nanostructured peroxidase. ► Self-assembled nano-cluster complex. ► 39% catalytic efficiency of native HRP. ► Good stability to high concentration of H2O2. A nano-cluster complex with highly efficient peroxide activity was constructed by self-assembly of nafion (NF) and cytochrome c (Cyt c) in 50mM phosphate buffer at 25°C. The UV–vis spectrometry, circular dichroism (CD) and transmission electron microscopy (TEM) methods were utilized for additional characterization of the nanostructured enzyme or artificial peroxidase (AP). The nano-cluster was composed of Chain-Ball structure, with an average ball size of approximately 40nm detected by TEM method. The Michaelis–Menten (Km) and catalytic rate (kcat) constants of the AP were obtained in 50mM phosphate buffer solution at pH 7.0 which are equal to 2.5±0.4μM and 0.069±0.001s−1 respectively. The catalytic efficiency of AP was evaluated to be 0.028±0.005μM−1s−1, which was 39±5% as efficient as the native HRP. The AP generated here can be used in place of HRP with high stability and activity.